Problem obcości: opozycja Rosja–Europa w kulturze rosyjskiej (XI–XIX w.) - Jedliński, Marek (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article analyzes the historical perspective of the formation of the opposition “friend or foe” in the Russian culture from the Middle Ages to the 19th century. Binary thinking has a universal dimension: it is present in every culture, particularly in traditional societies (in this case it is the opposition Russia–Europe). Hostility towards strangers is already noticeable in the Ruthenian tribes. The outsiders were seen as savages, as animals, and even as evil forces. It relates to the perception of the symbolic center of the world. It is recognizable in the work of Hilarion and the concept of Moscow as the Third Rome.